Correlation and predictive value of oxygenation and oxygen saturation indices in extremely preterm infants: a prospective study - Alanazi, Ibrahim; Algarni, Saleh S.; Alshreedah, Saad; Alotaibi, Naif; Sufyani, Mohammed; Alanazi, Sami S.; Alharthi, Abeer H.; Ghazwani, Abadi; Almutairi, Omar M.; Alkaabi, Maryam; Homedi, Abdulaziz; Ali, Ibrahim; et al. (Frontiers in Pediatrics, 2025)
AimsThis study aims to evaluate the association between the Oxygenation Index (OI) and the Oxygen Saturation Index (OSI) in extremely preterm infants. In addition, the study seeks to determine the predictive value of these indices for mortality in the first 7 days and Bronchopulmonary Dysplasia (BPD) at 36 weeks postmenstrual age (PMA).MethodsThis is a prospective observational study conducted at King Abdulaziz Medical City, Riyadh between October 2023 and May 2024, involving extremely preterm infants with clinical and ventilator data collected during the first 7 days of life. The predictive capabilities of OI and OSI for mortality within the first 7 days and BPD at 36 wks. PMA were assessed using Area Under the Curve (AUC) analysis, while associations between indices were explored through Spearman's correlation coefficient.ResultsThe study included 85 infants with a mean birth weight of 856 grams (SD = 243) and a mean gestational age of 26 weeks (SD = 1.8). There was a strong positive correlation between OI and OSI overall (r = 0.848, p < 0.001, n = 85), with similar findings in both surviving (r = 0.831, p < 0.001, n = 71) and non-surviving groups (r = 0.896, p < 0.001, n = 14). Bland-Altman plots showed a mean difference of 3 between OI and OSI for all infants, with limits ranging from −4 to +8. Tighter agreement was observed in survivors with a mean difference of 2 and limit from −4 to +7, while non-survivors showed a larger mean difference of 4.5 and wider limits of agreement from −8 to +17. Receiver Operating Characteristic (ROC) analysis for survival prediction focused on indices measured within the first 24 h, demonstrating high predictive accuracy. Additionally, the mean daily values for OI and OSI between Day 4 and Day 7 were found to be predictive of BPD at 36 wk. PMA.ConclusionsMeasurements of OI and OSI within the first 24 h effectively predict mortality in extremely preterm infants. Additionally, daily mean values of OI and OSI from day 4 to day 7 were predictive of BPD at 36 weeks PMA. Further research is needed to refine these diagnostic thresholds to enhance neonatal care outcomes.